Tunable and switchable dual wavelength lasers using optical fibre Bragg grating external cavities - Reilly S. P.; James, Stephen W.; Tatam, Ralph P. (Institution of Engineering and Technology (IET), 2002)
Two novel external cavity lasers are demonstrated experimentally. The first utilises a Bragg grating fabricated in highly birefringent optical fibre and offers the ability to switch between modes that are separated in polarisation and wavelength. The second utilises two spatially separate Bragg gratings fabricated in mono-mode fibre. Both can be used for tunable beat frequency generation.
Keywords: Bragg gratings; birefringence; fibre lasers; laser cavity resonators; laser modes; laser stability; laser tuning